The Effect of Fortification Cornmeal with Cherry (Muntingia Calabura) Leaf Extract on Resistant Starch, Digestibility and Glycemic Index - Suryani Une, Lisna Ahmad, Purnama Ningsih Maspeke (International Journal of Advanced Science and Technology, 2020)
The availability of processed foods from corn like cornmeal could become one of the solutions to reduce the high dependence of rice and other import foods so it could support the development of food diversification in the food security program. The processed corn could be used as a food alternative that good for health, especially for those who had the potential of an excess of the blood sugar (Diabetes mellitus). This is related to the glycemic index (GI) of corn low that is good for the health. Fortification with cherry leaf extract expected to improve resistant starch levels, decrease digestibility of cornmeal and pressed the absorption of sugar for diabetics Mellitus. The objective of this study was to determine of glycemic index values, resistant starch and digestibility of cornmeal fortified with cherry leaf extract. The study was conducted in experimental design used the completely randomized design with four treatments concentration of cherry leaves extract which is 0%, 20%, 30%, 40% respectively, that is fortified towards corn to know its effect on the glycemic index, resistant starch and digestibility. Glycemic index value has been analysed thoroughly in vivo, using eight respondents who have been selected based on normal body mass index. Resistant starch of cornmeal fortified by cherry leaves extract showed increased compared with the unfortified with the highest value obtained at 30% concentration extract and its digestibility had positive correlation with resistant starch. The lowest glycemic index of fortified cornmeal gained at 20% concentration cherry leaves extract for 77,18 mg/dl. Fortification of cherry leaves extract towards the cornmeal indicate the increased of resistant starch levels, lower digestibility and pattern of glucose absorption with the low glycemic index value.